KELAYAKAN USAHA AGROINDUSTRI BAWANG GORENG PALU DI KABUPATEN DONGGALA - Yulianti Yulianti; Nilam Sari (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The aim of the research was to identify the suitability of fried onion industry.  The research was carried out in 2007.  Samples of the fried onion industry in Palu were determined using a census method by taking all 17 fried onion industrial units existed in Donggala district. Analysis methods used were Net Present Value (NPV), Benefit Cost Ratio (BCR) and Internal Rate Return (IRR). The research results showed that based on production multiplication the fried onion industry returns was 19,500 kg year-1 with fried onion selling price of IDR 70,000 kg-1. Thus, the average of returns obtained was IDR 7,665,000year-1. The fried onion industry was financially suitable to be run and developed as indicated by NPV value of IDR 10,406,415,482, BCR value of 1.61, and IRR value of 576.13% or in other words NPV>0, BCR>1 and IRR>12.30%. The industry benefit obtained from the difference between the returns and costs was IDR 3,056,587,500 year-1 or IDR 245,715,625 month-1.  Factors affecting the industry benefit were the production quantity and costs spent for production facilities